2018
DOI: 10.1111/1753-0407.12645
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and branched‐chain amino acids: What is the link?

Abstract: Diabetes and branched-chain amino acids: What is the link?Branched-chain amino acids (BCAA) have increasingly been studied as playing a role in diabetes, with the PubMed search string "diabetes" AND "branched chain amino acids" showing particular growth in studies of the topic over the past decade (Fig. 1). In the Young Finn's Study, BCAA and, to a lesser extent, the aromatic amino acids phenylalanine and tyrosine were associated with insulin resistance (IR) in men but not in women, whereas the gluconeogenic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
127
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(137 citation statements)
references
References 43 publications
(44 reference statements)
7
127
0
3
Order By: Relevance
“…These findings were also observed in our study, BCAA had positively related to total cholesterol and glucose, which were reduced in inulin groups. The risk of future T2D was substantially increased with the elevation of a small cluster of circulating amino acids, including BCAAs and aromatic amino acids [54]. As the activation of the mammalian target of rapamycin (mTOR) and its downstream effectors, S6 kinase and insulin receptor substrate-1, the elevating BCAA may disrupt insulin signaling, thus triggering T2D [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…These findings were also observed in our study, BCAA had positively related to total cholesterol and glucose, which were reduced in inulin groups. The risk of future T2D was substantially increased with the elevation of a small cluster of circulating amino acids, including BCAAs and aromatic amino acids [54]. As the activation of the mammalian target of rapamycin (mTOR) and its downstream effectors, S6 kinase and insulin receptor substrate-1, the elevating BCAA may disrupt insulin signaling, thus triggering T2D [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism responsible remains unclear, but may be connected to changes in the intestinal microenvironment 33 or the metabolism of gut flora, such as that of short-chain fatty acids, which have been suggested to strengthen the gut barrier, 34 or branched-chain amino acids, which have also been associated with increased INS sensitivity after bariatric surgery. 35 Recently, Thaiss et al 36 revealed that improved glycemia may contribute to restored gut integrity through a mechanism involving the glucose transported GLUT2 on the basolateral membranes of enterocytes. Based on this, we speculate that the improvement in gut permeability can be partly attributed to the rapid control of glucose levels after RYGB surgery.…”
Section: Discussionmentioning
confidence: 99%
“…As another example, BCAA have been described to be altered in human diabetes, a risk factor for Alzheimer's disease [242]. Preclinical studies have shown that the accumulation of these amino acids in brain promotes the phosphorylation of Tau proteins, which are involved in the development of Alzheimer [243]. Thus, the identification of alterations in these biomarkers and their precursors would be of high relevance.…”
Section: Future Perspectivesmentioning
confidence: 99%